The journey to reporting child protection violations in sport: Stakeholder perspectives - Tuakli-Wosornu, Yetsa A.; Kirby, Sandi L.; Tivas, Anne; Rhind, Daniel (Frontiers in Psychology, 2023)
Sport is a context within which human and children’s rights should be respected, promoted, and protected. Yet, research and high-profile cases demonstrate that this is not always the case. To understand the existence (or not) of reporting mechanisms for child protection violations in sport, as well as how existing reporting and response systems operate, the authors, with the support of the Centre for Sport and Human Rights, conducted research on current abuse disclosure and reporting pathways in sport. The purpose was two-fold: to describe global child protection systems and reporting mechanisms, and to identify major areas of stakeholder concern, in terms of effective case resolution, healing, and children’s experiences along reporting pathways in sport. Two sources of evidence were tapped. First, a rapid evidence assessment consisting of a literature review and an exploratory survey with 112 global stakeholders was conducted. Second, focus group interviews informed by the evidence assessment were held with 9 athletes with lived experiences of abuse in youth sport and 13 global human and children’s rights experts primarily working outside of sport. Through this emergent research, a ‘pathway’ or ‘journey’ to incident reporting in sport was developed, summarized as 5 ‘Rs’: Readiness, Recognition, disclosure and Reporting, Response, and Remedy, which are similar but not identical to existing trauma frameworks. Each stage of the reporting journey appears to be influenced by a range of contextual, organizational, relational, and individual factors. All told, the disclosure of child protection violations in sport is a complex and dynamic process where myriad factors interact to influence outcomes, including healing. Key recommendations include: a) establishing a global Safety Net Environment in sport practice with varying applications from region to region, b) building bridges with specific partner organizations to enhance child protection and safeguarding work in sport and c) bringing safeguarding to unregulated sporting environments.